CEO bias and product substitutability in oligopoly games - Elizabeth Schroeder; Carol Horton Tremblay; Victor J. Tremblay (Games, 2022)
We investigate why a firm might purposefully hire a chief executive officer (CEO) who under- or over-estimates the degree of substitutability between competing products. This counterintuitive result arises in imperfect competition because CEO bias can affect rival behavior and the intensity of competition. We lay out the conditions under which it is profitable for owners to hire biased managers. Our work shows that a universal policy that effectively eliminates such biases need not improve social welfare.
Keywords: 330; behavioral economics; Bertrand model; Cournot model; Cournot-Bertrand model; firm objectives